OXPHOS remodeling in high-grade prostate cancer involves mtDNA mutations and increased succinate oxidation - Schöpf, Bernd; Weissensteiner, Hansi; Schäfer, Georg; Fazzini, Federica; Charoentong, Pornpimol; Naschberger, Andreas; Rupp, Bernhard; Fendt, Liane; Bukur, Valesca; Giese, Irina; Sorn, Patrick; Sant’Anna-Silva, Ana Carolina; et al. (Nature communications, 2020)
Rewiring of energy metabolism and adaptation of mitochondria are considered to impact on prostate cancer development and progression. Here, we report on mitochondrial respiration, DNA mutations and gene expression in paired benign/malignant human prostate tissue samples. Results reveal reduced respiratory capacities with NADH-pathway substrates glutamate and malate in malignant tissue and a significant metabolic shift towards higher succinate oxidation, particularly in high-grade tumors. The load of potentially deleterious mitochondrial-DNA mutations is higher in tumors and associated with unfavorable risk factors. High levels of potentially deleterious mutations in mitochondrial Complex I-encoding genes are associated with a 70% reduction in NADH-pathway capacity and compensation by increased succinate-pathway capacity. Structural analyses of these mutations reveal amino acid alterations leading to potentially deleterious effects on Complex I, supporting a causal relationship. A metagene signature extracted from the transcriptome of tumor samples exhibiting a severe mitochondrial phenotype enables identification of tumors with shorter survival times. The re-wiring of the metabolic machinery is a common feature in cancer. Here, the authors show, using paired normal and prostate cancer samples that the cancer samples exhibit a shift to succinate respiration, which is associated with elevated levels of mitochondrial DNA mutations.